Jesus mit dem Judenhut: Ikonographische Notizen - Bachmann, Michael (Zeitschrift für Theologie und Kirche, 2003)
Up to now, the only reference to "Jesus with the Jewish hat" in the relevant literature has consisted of one or two "illustrations" in the Emmaus story (Luke 24:13—35). After presenting a short overview of the iconographic and medieval context of the Jewish hat, the author shows that there is a large number of miniatures and woodcuts related to another pericope, Apocalypse 6:1—8, to be taken into consideration (among other perhaps even Dürer's famous print on the horsemen of the Apocalypse). In most of these, all four horsemen are wearing a Jewish hat, and in each of the early documents at least one has to think of Christ, according to the Berengaudus interpretation of the Apocalypse. The awareness of these documents was altered mainly by Luther's interpretation of the verses ("four plagues").